(untitled) (Global Journal of Management and Business Research, 2019)
The paper has as g oal, to present some of the main and most acceptable methods to significate the power to tax limitating concepts. Will be revealed that, even though the Constitution doesn#x2019;t expressly define the power to tax limitating concepts, it doesn#x2019;t mean that the interpreter is freely authorized to do so. On the contrary, the lawyer must act inside the constitutional limits, otherwise his or her interpretation will become unconstitutional and incorrect. It will be demonstrated that the infra-constitutional legislation, the legal literature and the case-law provide some reliable interpretative methods to help the interpreter finding a correct meaning of the power to tax limitating concepts. Each one of these methods will be analyzed, with their legal basis, uses, qualities and faults. By the end of the paper, it will be proved that the lawyer decreases the chances to disrespect the Constitution, by using those methods correctly.